2015
DOI: 10.1016/j.ultsonch.2015.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and kinetic study of the ultrasonic degradation of locust bean gum in aqueous saline and salt-free solutions

Abstract: The ultrasonic degradation of locust bean gum (LBG) in aqueous solutions has been studied at 25°C for ultrasonication times up to 120 min. Although LBG is not a polyelectrolyte, the degradation extent and kinetics were found to be somewhat sensitive to the ionic conditions in solution, and this is attributed to changes in molecular conformation that can occur in different salt environments. Ultrasonic degradation was tracked by rheological measurements that lead to the determination of intrinsic viscosity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…After sonication, since the molecular chains became shorter, the influence of molecular interaction on intrinsic viscosity became limited and less important. Such phenomenon was also observed in xanthan gum [21], locust bean gum [22] and polysaccharides from Porphyra yezoensis [23].…”
Section: Resultsmentioning
confidence: 75%
“…After sonication, since the molecular chains became shorter, the influence of molecular interaction on intrinsic viscosity became limited and less important. Such phenomenon was also observed in xanthan gum [21], locust bean gum [22] and polysaccharides from Porphyra yezoensis [23].…”
Section: Resultsmentioning
confidence: 75%
“…They showed that when NaCl was used, the degradation was more effective compared to the Na 2 SO 4 usage. 29 In another study of Li and Feke, it was concluded that an addition of NaCl to the solution was more effective than Na 2 SO 4 during the ultrasonic xanthan degradation. They reported that xanthan exhibited a more compacted form in the Na 2 SO 4 solution.…”
Section: When the Nano 3 -Pdadmac Solution Was Irradiatedmentioning
confidence: 96%